The Effect of Static Magnetic Field on Methanogenesis in the Anaerobic Digestion of Municipal Sewage Sludge - Marcin Zieliński; Marcin Dębowski; Joanna Kazimierowicz (Energies, 2021)
The present study aimed to determine the effect of a 17.6 mT static magnetic field (SMF) on the efficiency of anaerobic digestion (AD) of municipal sewage sludge (MSS). The SMF had a significant impact on methane (CH4) production efficiency, the levels of fermentation rate (ηFMSS) vs. removal rate (ηVS), and the structure of the anaerobic bacteria consortium, but it did not affect cumulative biogas production. The highest CH4 yield (431 ± 22 dm3CH4/kgVS) and the highest methane content in the biogas (66.1% ± 1.9%) were found in the variant in which the SMF exposure time was 144 min/day. This variant also produced the highest ηFMSS and ηVS values, reaching 73.8% ± 2.3% and ηVS 36.9% ± 1.6%, respectively. Longer anaerobic sludge retention time in the SMF area significantly decreased AD efficiency and caused a significant reduction in the number of methanogens in the anaerobic bacteria community. The lowest values were observed for SMF exposure time of 432 min/day, which produced only 54.8 ± 1.9% CH4 in the biogas. A pronounced reduction was recorded in the Archaea (ARC915) and Methanosaeta (MX825) populations in the anaerobic sludge, i.e., to 20% ± 11% and 6% ± 2%, respectively.